2006
DOI: 10.1111/j.1525-1497.2006.00409.x
|View full text |Cite
|
Sign up to set email alerts
|

Using the patient health questionnaire-9 to measure depression among racially and ethnically diverse primary care patients

Abstract: OBJECTIVE:The Patient Health Questionnaire depression scale (PHQ-9) is a well-validated, Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition (DSM-IV) criterion-based measure for diagnosing depression, assessing severity and monitoring treatment response. The performance of most depression scales including the PHQ-9, however, has not been rigorously evaluated in different racial/ethnic populations. Therefore, we compared the factor structure of the PHQ-9 between different racial/ethnic groups a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
451
5
9

Year Published

2008
2008
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 605 publications
(494 citation statements)
references
References 38 publications
29
451
5
9
Order By: Relevance
“…Prevalence of depression among T2D patients is high when compared with general population (Huang et al ., 2006; Heckbert et al ., 2010; Al‐Amer et al ., 2011), varying from 5% to 60% according to the results of a previous meta‐analysis (Anderson et al ., 2001). Our results found that more than one in 10 patients presented moderately severe or severe depression; although when the usual PHQ‐9 cutoff of 10 was used, prevalence increased to 33.6% (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Prevalence of depression among T2D patients is high when compared with general population (Huang et al ., 2006; Heckbert et al ., 2010; Al‐Amer et al ., 2011), varying from 5% to 60% according to the results of a previous meta‐analysis (Anderson et al ., 2001). Our results found that more than one in 10 patients presented moderately severe or severe depression; although when the usual PHQ‐9 cutoff of 10 was used, prevalence increased to 33.6% (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…The PHQ-9 is a nine-item questionnaire that asks respondents to indicate the frequency with which they experience each of the nine symptoms considered in the diagnostic criteria for major depression [28]. The PHQ-9 has been shown to be a valid and reliable measure of depressive symptoms in patients with a variety of medical conditions [11,14,19].…”
Section: Methodsmentioning
confidence: 99%
“…The PHQ-9 can be self-administered or interviewer-administered and is well-validated in the United States as a dual-purpose instrument that yields both a measure of depression severity and criteria-based diagnoses of DSM-IV depressive disorders: major depressive disorder (MDD), other depressive disorder (ODD), and any depressive disorder (i.e., MDD or ODD). 25,26 It has also been successfully used in diverse populations, specifically those with HIV. 26,27 Rather than using the differences in diagnoses of ODD and MDD, we dichotomized the depressive disorder diagnoses (depressive disorder versus minimal or no depressive symptoms), since the nine items from the instrument provide a method to calculate a count of symptoms and severity to identify these disorders.…”
Section: Methodsmentioning
confidence: 99%